Estrus response and pregnancy rate of swamp buffalo: The use of multivitamins in different estrus synchronization hormone protocols. - Syaiful, Ferry Lismanto; Jaswandi, Jaswandi; Mundana, Mangku; Yendraliza, Yendraliza; Udin, Zaituni (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: This study aims to determine the effect of using multivitamins in different estrus synchronization hormone protocols on estrus response, estrus onset, estrus duration, estrus intensity, and pregnancy rate in swamp buffalo. Materials and Methods: This study used 30 post-partum adult buffalo, with three estrus synchronization methods treated: 1. Conventional plus Prostaglandin F2 α (PGF2α-PGF2α + multivitamin)-AI; 2. Co-synch plus Gonadotropin-releasing hormone (GnRH-PGF2α + multivitamin)-AI; 3. Combination of hormone plus (Estrogen-Progesterone-PGF2α + multivitamin)-AI. Research variables include estrus response, estrus onset, estrus duration, estrus intensity, and pregnancy rate. Data were analyzed using the chi-square test using the Statistical Package for the Social Sciences 23.0 program. Results: The results showed that the use of multivitamins in different estrus synchronization hormone protocols resulted in an estrous response reaching 100%. The onset of estrus in the three treatments [Treatment-1 (T1); Treatment-2 (T2); Treatment-3 (T3)] was 25.8; 27.6; 23.9 h, estrus duration: 21.0; 21.6; 21.92 h, estrus intensity: 25.8; 27.6; 32.6 h, and the pregnancy rate for buffalo reaches 80%. Conclusion: Based on the results of this study, the use of multivitamins in different estrus synchronization hormone protocols is effective in optimizing the swamp buffalo’s estrus response; the estrus duration is longer, the estrus onset is faster, and the estrus intensity is higher. It can even optimize the increase in swamp buffalo pregnancy rates. J. Adv. Vet. Anim. Res., 11(3): 729–737, September 2024 http://doi.org/10.5455/javar.2024.k824